2012
DOI: 10.1007/s10552-012-9984-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D and risk of breast cancer: results of a large population-based case–control study in Mexican women

Abstract: The results of this large population-based case-control study indicate an inverse association between circulating vitamin D levels and breast cancer risk among pre- and postmenopausal Mexican women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
(78 reference statements)
2
26
1
1
Order By: Relevance
“…The current study is among the first, to our knowledge, to evaluate the association between serum 25(OH)D and breast cancer in women residing in Saudi Arabia, an area of high UV sunlight exposure, but potentially low vitamin D status related to skin type and cultural practices of dress. A study in Mexican women showed a 47% reduction in breast cancer risk in women with circulating concentrations of 25(OH)D .30 mg/mL (36). A study of women in the military did not show a significant relation between vitamin D status and breast cancer; however, among women sampled within 90 d of diagnosis, women in the lowest quintile had an OR of 3.3 for incident breast cancer (37) similar to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…The current study is among the first, to our knowledge, to evaluate the association between serum 25(OH)D and breast cancer in women residing in Saudi Arabia, an area of high UV sunlight exposure, but potentially low vitamin D status related to skin type and cultural practices of dress. A study in Mexican women showed a 47% reduction in breast cancer risk in women with circulating concentrations of 25(OH)D .30 mg/mL (36). A study of women in the military did not show a significant relation between vitamin D status and breast cancer; however, among women sampled within 90 d of diagnosis, women in the lowest quintile had an OR of 3.3 for incident breast cancer (37) similar to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Several observational studies and one RCT, suggest supplementation with vitamin D+calcium reduced cancer risk more than supplementation with vitamin D alone [24],[13],[25],[26]. Thus, to determine the effect of vitamin D alone, either the effect of calcium supplementation alone has to be determined if calcium supplementation is given solely to the treatment arm, as was the case in the later Lappe study [13], or both arms should receive calcium supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Mexican women with serum vitamin D levels < 20 ng/ml (defined as cutoff value for deficiency) had a higher risk of BC than women with a level > 20 ng/ml. In addition, a significant inverse dose-response was observed at higher levels of vitamin D associated with lower risk of BC 55 . Similarly, higher serum levels of vitamin D (> 27.3 ng/ml) were significantly inversely associated with lower percent mammographic density among young Mexican women with BMI < 27 kg/m 2 (median value), suggesting that some groups of women may benefit from vitamin D supplementation 56 .…”
Section: Vitamin Dmentioning
confidence: 92%